Aligning Sustainable Development Goals With TVET: Evidence from Policy and Practice in Nepal - Aryal, Baikuntha Prasad (Journal of Training and Development, 2026)
Nepal has committed to achieving the targets of the Sustainable Development Goals by 2030, and, in line with this, all policies and programs are developed and implemented. Technical vocational education and training (TVET) is also seen as a means to enhance employability, income generation, and entrepreneurship by developing competent human resources with the required skills and competencies. This paper examines TVET policies and practices, specifically their implementation modality, as they relate to SDG4 and SDG8, using a qualitative approach to identify further strategies for the effective implementation of TVET policies in line with the SDG targets. In the same way, the paper highlighted to what extent TVET policies and practices aligned with SDGs and what gaps remain in achieving SDGs targets, with major issues and challenges in the implementation and governance of existing TVET programs. Finally, the paper explored an appropriate way forward for achieving the SDGs, along with ways to address the challenges. It is expected that the paper will help to identify the strategies for TVET in Nepal to achieve the SDG targets by 2030.